Análise de uma experiência de atitudes comunicativas entre mãe e adolescente surdocega: construção de significados compartilhados - Cambruzzi, Rita de Cássia Silveira (2007)
The objective of this paper was to identify and analyze the communicative attitudes between a mother and her deafblind adolescent daughter, and also to contribute and promote the development of significant communication between them. In order for this to happen, supporting procedures were employed throughout this research, fomenting the mother as mediator of the process, making her aware of the different communication methods available and teaching her how to apply them to her natural environment, as well as to the social one. The results show significant differences. However, there is need of a broader connection to be established the family, so that the program to be implemented be consolidated in the execution of the activities and, as a consequence carry out the construction process of shared meaning. The journey that begins from this point on seems long. However, the first paces have already been established, renewing our persevering forces